A syndrome featuring developmental disorder of the nervous system induced by a novel mutation in the TCF20 gene, rarely concurrent immune disorders: a case report - Huang, Si; Xu, Jiaxin; Li, Yiyang; Mo, Wenhui; Lin, Xiuwen; Wang, Yajun; Liang, Fujian; Bai, Yan; Huang, Guochun; Chen, Jing; Xin, Jing; Ma, Guoda (Frontiers in Genetics, 2023)
Background: The expression of TCF20 is the most widespread in brain tissue. TCF20 depletion or mutation can affect the proliferation and differentiation of embryonic neurons, leading to developmental disorder of the central nervous system and subsequent rare syndrome featuring neuropsychiatric symptoms. Case presentation: Here, we report a 3-year-old boy carrying a novel frameshift mutation in TCF20, c.1839_1872del (p.Met613IlefsTer159), resulting in multisystem disease. In addition to symptoms of neurodevelopmental disorder, a large head circumference, special appearance, overgrowth, abnormal testicular descent. Remarkably, previously unreported symptoms of the immune system (e.g., hyperimmunoglobulinemia E [hyper-IgE], immune thrombocytopenic purpura, cows milk protein allergy, and wheezy bronchitis) were present. Conclusions: This study broadens the mutation spectrum of the TCF20 and the phenotypic spectrum of TCF20-associated disease.